Lost and Found : Market Access and Public Debt Dynamics - Cottarelli, Carlo (IMF Working Papers; Working Paper, 2016)
The empirical literature on sovereign debt crises identifies the level of public debt (measured as a share of GDP) as a key variable to predict debt defaults and to determine sovereign market access. This evidence has led to the widespread use of (country-specific) debt thresholds to assess debt sustainability. We argue that the level of the debt-to-GDP ratio, whose use is justified on a theoretical and empirical ground, should not be the only fiscal metric to assess the complex relationship between public debt and debt defaults/market access. In particular, we show that, in a large panel of emerging markets, the dynamics of the debt ratio plays a critical role for market access. In particular, given a certain level of debt, a steadily declining debt ratio is associated with a lower probability of debt distress/market loss and with a higher likelihood of market re-access once access had been lost.